Measuring cost of illness analysis of diarrhoeal diseases in north-western Nigeria - Salihu, Akbar; Suleiman, Hassan; Ibrahim, Muhammad (International Journal of Health, 2017)
Background: Global estimates of morbidity due to diarrhoeal diseases stood at 1.7 billion cases per year, leading to a mortality rate of 760 000/year among children under five. These figures have considerable consequences for individuals, families and the society in the form of social disruption, lost economic opportunities and health costs.Objectives: This study sought to measure the cost of illness analysis of diarrhoeal diseases among patients attending infectious disease hospital, Kano. It is focused on those specifically diagnosed with diarrhoeal diseases out of the general population of patients with infectious diseases.Methods: The prevalence-based approach was used to measure the cost of managing diarrhoeal diseases from the period of September 2015 to March 2016.Results: Utilizing primary and secondary data, it was discovered that the average amount (in Naira) needed for managing diarrhoeal disease at the center to be 5100.8 naira, direct medical cost was 917 naira, direct non-medical cost was 294.8 naira and indirect cost account for the highest at the cost of 3889 naira.Conclusions: This study provides policy makers with valid information that could be useful in health budget planning and implementation.